Pengaruh Promosi dan Kualitas Produk terhadap Keputusan Pembelian Produk Lipstik Wardah dengan Brand Image sebagai Variabel Intervening - Dwi Nur Aini; Ika Indriasari; Henry Casandra Gultom (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the influence of promotion and product quality on purchasing decisions for Wardah lipstick products with brand image as an intervening variable. This study is motivated by the decline in Wardah lipstick sales in the last five years even though demand for cosmetic products, especially lipstick, continues to increase. The research method used is a qualitative approach with a survey method. The sample of this study was 100 respondents who are Wardah lipstick users in Semarang City, selected using a purposive sampling technique. The data analysis technique used Partial Least Square (PLS) with the help of SmartPls 4.0 software. The results of the study indicate that promotion has a significant negative effect on purchasing decisions, while product quality has a significant positive effect on purchasing decisions. Brand image is also proven to have a significant positive effect on purchasing decisions and is able to mediate the influence of promotion and product quality on purchasing decisions. These findings confirm that Wardah's promotional strategy needs to be evaluated, while improving product quality and strengthening brand image remain key in influencing consumer purchasing decisions.